Discrepancies in dyadic coping: associations with distress and quality of life in couples facing early stage dementia - Muijres, Peter; Weitkamp, Katharina; Bodenmann, Guy; Jenewein, Josef (Frontiers in Psychology, 2023)
Objectives Due to an aging population, the number of persons living with dementia (PWDs) is increasing worldwide. Romantic partners, as informal caregivers (IC) of PWDs, are often adopting additional tasks. The concept of dyadic coping (DC) addresses how couples cope with stress together. For dyadic coping to be successful, efforts of both partners should be equal. The current study examines how discrepancies in PWDs and ICs perspectives on DC relate to distress and quality of life in each partner within couples facing early stage dementia (ESD). Methods A total of 37 mixed-sex couples including one partner with ESD completed self-report questionnaires. Discrepancies in reciprocity (comparing provided or received levels of DC between partners), equity (each partner balancing own levels received and provided), and congruence (the agreement about levels of DC exchanged between partners) and their covariation with distress and quality of life (QoL) of each partner were measured. Results Both partners indicated a discrepancy in reciprocity: PWDs reported receiving more DC than ICs reported receiving, which was associated with higher QoL in PWDs and lower QoL in ICs. Inequities were found in ICs only, who reported receiving less DC, than providing. No relation between inequities and distress or QoL was found. ICs reported more incongruencies than PWDs did, which was associated with higher QoL and less depression in partners. Discussion A redivision of tasks and roles in the early stage of dementia is associated with different experiences and views between partners. Whereas ICs take over most household and care tasks within the couple, their effort was considered less helpful by PWDs than by ICs. A high care burden is associated with a compromised quality of ICs’ social life and living conditions. The clinical implications of the results are discussed.